El Excentrico, 1964-08-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
August 5, 1964 [5 de Agosto de 1964]. Ano 14, No 20. Cover has a picture of Hank Coca and a advertisement of the Furniture Discount House. The headline reads "Thank you Mr and Mrs Public."